The Dangers of Unregulated Economic Ideologies in Indonesia and Kazakhstan: Lessons from the Timah and Kazatomprom Cases - Siahaan, Rio Andre Winter; Meliala, Aurora Jillena; Akhmetova, Assem (TANJUNGPURA LAW JOURNAL, 2025)
AbstractEconomic ideology plays a crucial role in shaping a country"™s economy, but its implementation often faces internal and external obstacles, leading to systems influenced by socialist or capitalist ideologies. In certain cases, such as the Timah case in Indonesia and Kazatomprom in Kazakhstan, the dogmatic nature of economic regulations harms both local communities and businesses. Corporations, too, become victims of these impractical and overly ideological frameworks. This article aims to analyze how the incomplete resolution of economic ideology in practical regulations has led to uncertainty in the business world, making it vulnerable to criminalization. It examines the historical development of Indonesia's economic identity, which traditionally viewed land, labor, and capital as sources of prosperity but has struggled to fully realize this vision. Through a comparative analysis of the Timah and Kazatomprom cases, the article highlights the dangers of unregulated economic ideologies and calls for reforms to create more effective legal frameworks that align with Indonesia"™s native economic principles and tackle corruption.AbstrakIdeologi ekonomi memainkan peran penting dalam membentuk ekonomi suatu negara, tetapi implementasinya sering menghadapi hambatan internal dan eksternal, yang mengarah pada sistem yang dipengaruhi oleh ideologi sosialis atau kapitalis. Dalam kasus-kasus tertentu, seperti kasus Timah di Indonesia dan Kazatomprom di Kazakhstan, peraturan ekonomi yang dogmatis telah merugikan masyarakat dan bisnis lokal. Korporasi juga menjadi korban dari kerangka kerja yang tidak praktis dan terlalu ideologis ini. Artikel ini bertujuan untuk menganalisis bagaimana penyelesaian ideologi ekonomi yang tidak lengkap dalam peraturan praktis telah menyebabkan ketidakpastian dalam dunia bisnis, sehingga rentan terhadap kriminalisasi. Artikel ini mengkaji perkembangan historis dari identitas ekonomi Indonesia, yang secara tradisional memandang tanah, tenaga kerja, dan modal sebagai sumber kemakmuran, tetapi telah berjuang untuk sepenuhnya mewujudkan visi ini. Melalui analisis komparatif terhadap kasus Timah dan Kazatomprom, artikel ini menyoroti bahaya ideologi ekonomi yang tidak diatur dan menyerukan reformasi untuk menciptakan kerangka hukum yang lebih efektif yang selaras dengan prinsip-prinsip ekonomi asli Indonesia dan mengatasi korupsi.